A compact substrate integrated waveguide backed self‐quadruplexing antenna for C‐band communication. Issue 10 (2nd August 2020) - Dash, Sounik Kiran Kumar; Cheng, Qingsha S.; Barik, Rusan Kumar
Abstract: This article presents a simple, compact, and lightweight substrate integrated waveguide (SIW) backed self‐quadruplexing antenna for quad‐band applications. The design procedure is straightforward. Topside of the SIW cavity is modified to form four patches of different lengths which are fed separately by four 50‐Ω microstrip feed lines and operate at 5.14, 5.78, 6.74, and 7.74. It attains 4.1, 4.96, 6.2, and 6.1 peak gain at the above frequencies, respectively. The observed front‐to‐back‐ratio is more than 17.5 dB and the isolation level is above 28 dB. This antenna topology allows to redesign each resonant frequencies as per application requirement using a single parameter and without disturbing other performances. Design guidelines for developing the proposed antenna are provided. A prototype antenna is fabricated using RT‐Duroid (5870) substrate and characterized for validation. The proposed antenna is suitable for handheld microwave devices for C‐band communication.